Quality indicators of supportive care for patients with cancer undergoing treatment: a systematic review - Okuyama, Ayako; Kuwabara, Mai; Zenda, Sadamoto (BMC cancer, 2025)
Patients need to be supported in combining treatment with daily life. However, measurement of supportive care indicators related to treatment-related side effects is under-reported. This review aimed to identify a list of quality indicators for managing cancer treatment-induced toxicities for adult patients with cancer. A review was conducted on PubMed, the Cumulative Index to Nursing and Allied Health Literature, the Cochrane Database of Systematic Reviews, and Embase from September 26, 2013 to December 26, 2023. Published English articles that developed or analyzed quality indicators of managing cancer treatment-induced toxicities for adult patients with cancer were selected. The identified indicators were classified according to Donabedian's model for quality of care in healthcare. Forty-two indicators (4 structural, 27 process, and 11 outcome indicators) in 18 articles were identified. Eight articles (44.4%) were from North America, four (22.2%) from Europe, two (11.1%) from Oceania, two (11.1%) from Asia, and one (5.6%) from Africa; 64.3% of the indicators were process indicators based on guidelines. The prevalence of patient symptoms determined using a patient-reported outcome measure was proposed as an outcome indicator. In seven studies (38.9%), these indicators were selected by multidisciplinary experts. None of the studies involved patients or family members in the indicator selection process. The quality of supportive care should be improved by measuring these indicators, considering the patient's needs for supportive care at each hospital such that patients can continue their lives while undergoing treatment.